The Effect of Examiner Variability on Multiple Canine Stifle Kinematic Gait Collections in a 3‐Dimensional Model. Issue 5 (4th December 2014) - Torres, Bryan T.; Gilbert, Peter J.; Reynolds, Lisa R.; Fu, Yang‐Chieh; Navik, Judith A.; Sornborger, Andrew; Budsberg, Steven C.
Abstract : Objective: To evaluate examiner variability in a superficial skin marker model of canine stifle kinematics. Study Design: Experimental. Animals: Six clinically normal dogs. Methods: Dogs had 11 retroreflective markers fixed to the skin on the right hindlimb. Dogs were trotted 5 times through the calibrated testing space and this was repeated on 4 different testing days. Examiner A applied all markers to a dog and collected 6 good trials for analysis. The markers were then removed and Examiner B immediately repeated the process on the same dog. This was repeated for each dog on the 4 testing days. The dogs were trotted at a velocity of 1.70–2.10 m/s through the testing space to obtain the dynamic data sets. Comparisons were performed with Fourier analysis and Generalized Indicator Function Analysis (GIFA). Significance was set at P  < .05 for all comparisons. Results: Fourier analysis and GIFA found differences within and between examiners. Fourier analysis found no differences in sagittal and transverse planes for the experienced (A) and novice examiner (B), respectively. Fourier analysis detected fewer differences for the experienced examiner (A). Conclusion: Variability occurs within and between examiners using the same kinematic model. Transverse and frontal plane kinematics produce variable results between examiners. Prior experience with the model reduces the amount of variability and results in consistent and repeatable sagittal plane kinematic data collection.